2009
DOI: 10.1136/jnnp.2008.162784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immigration on multiple sclerosis sex ratio in Canada: the Canadian Collaborative Study

Abstract: MS sex ratio in immigrants to Canada is increasing but variable by region of origin and influenced by age at migration. The findings highlight the importance of environmental effect(s) in MS risk, which are likely gender-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 38 publications
7
37
1
1
Order By: Relevance
“…A study performed in Canada showed a gradual increase in the rate of female to male ratio in a cohort of immigrants. The gender ratio increased gradually, until it was similar to the ratio of patients born in Canada, and the trend was more significant in the patients immigrating to Canada from southern Europe at an age younger than 21 years [11] .…”
Section: Introductionmentioning
confidence: 85%
“…A study performed in Canada showed a gradual increase in the rate of female to male ratio in a cohort of immigrants. The gender ratio increased gradually, until it was similar to the ratio of patients born in Canada, and the trend was more significant in the patients immigrating to Canada from southern Europe at an age younger than 21 years [11] .…”
Section: Introductionmentioning
confidence: 85%
“…Although sexual dimorphism of TLR effects on disease has not been previously reported, postpubertal mice show sex differences in cytokine responses to TLR ligands, with females producing less IL-1 in response to the TLR2 ligand lipoteichoic acid (72), and it is a typical feature of both EAE (73-76) and MS [reviewed in Orton et al (77)]. Paradoxically, although the incidence and severity of MS is generally higher in women, it is also more readily affected by environmental change (77). Although these data do not contribute to understanding the greater susceptibility of women to autoimmunity, they do provide a potential mechanism by which environmental factors could play a greater role in the prevalence of disease in women than in men.…”
Section: Role Of Central Regulatory T Cells In Modulating Passivementioning
confidence: 94%
“…In 1999, Bencsik et al (15) reported that the female/male ratio was 1:2.75 in the MS population of the county and 1:1.09 in the overall county population. These results are in accordance with the literature finding of a higher occurrence of MS in women and with those that show an increasing tendency (26,27).…”
Section: Discussionsupporting
confidence: 83%